Inter-rater and Intra-rater Reliability of the Chinese Version of the Action Research Arm Test in People With Stroke - Zhao, Jiang-Li (Front Neurol, 2019)
Purpose: To detect the inter-rater and intra-rater reliability of the Chinese version of the Action Research Arm Test (C-ARAT) in patients recovering from a first stroke. Methods: Fifty-five participants (45 men and 10 women) with a mean age of 58.67 ± 12.45 (range: 22–80) years and a mean post-stroke interval of 6.47 ± 12.00 (0.5–80) months were enrolled in this study. To determine the inter-rater reliability, the C-ARAT was administered to each participant by two raters (A and B) with varying levels of experience within 1 day. To determine intra-rater reliability, rater A re-administered the C-ARAT to 33 of the 55 participants on the second day. Intra-class correlation coefficients (ICCs) and Bland–Altman plots were used to analyse the inter-rater and intra-rater reliability. Results: Regarding inter-rater reliability, the total, grasping, gripping, pinching, and gross movement scores received respective ICCs of 0.998, 0.997, 0.995, 0.997, and 0.960 (all p < 0.001), indicating excellent inter-rater reliability in stroke patients. Regarding intra-rater reliability, the corresponding ICCs were 0.987, 0.980, 0.975, 0.944, and 0.954 (all p < 0.001), again indicating excellent intra-rater reliability. The Bland–Altman plots yielded a mean difference of 0.15 with 95% limits of agreement (95%LOA) ranging from −2.16 to 2.46 for the inter-rater measurements and a mean difference of −1.06 with 95%LOA ranging from −6.43 to 4.31 for the intra-rater measurement. The C-ARAT thus appeared to be a stable scoring method. Conclusions: The C-ARAT yielded excellent intra-rater and inter-rater reliability for evaluating the paretic upper extremities of stroke patients. Therefore, our results supported the use of the C-ARAT in this population.